Range of Motion of the Upper Cervical Spine: flexion, extension, lateral bending, and axial rotation - Lorente, Ana I.; Hidalgo García, César; Rodríguez Sanz, Jacobo; Maza Frechín, Mario; Pérez Bellmunt, Albert (Jornada de Jóvenes Investigadores del I3A, 2020)
Instability is a serious and life-threatening diagnosis in the upper cervical spine (occiput-atlas-axis), and a depth understanding of normal range of movement is required for clinical manual evaluation. To improve this knowledge, ten upper cervical spine specimens have been tested in flexion, extension, lateral bending, and axial rotation.